The epidemiology of yellow fever in Africa - Mutebi, John-Paul; Barrett, Alan D. T. (Microbes and infection, 2002)
Yellow fever (YF) is still a major public heath problem, particularly in Africa, despite the availability of a very efficacious vaccine. The World Health Organization estimates that there are 200,000 cases ofYF annually, including 30,000 deaths, of which over 90% occur in Africa. In the past 15 years, the number of YF cases has increased tremendously, with most of the YF activity in West Africa. This increase in YF activity is in part due to a breakdown inYF vaccination and mosquito control programs. Five genotypes ofYF virus have been found in Africa, and each genotype circulates in a distinct geographical region.West Africa genotype I, found in Nigeria and surrounding areas, is associated with frequent epidemics, whereas the three genotypes in East and Central Africa are in regions where YF outbreaks are rare. Other factors, including genetic and behavioral variation among vector species, are also thought to play a role in the epidemiology of YF in Africa.